Bayesian logical neural networks for human-centered applications in medicine - Diaz Ochoa, Juan G.; Maier, Lukas; Csiszar, Orsolya (Frontiers in Bioinformatics, 2023)
Background: Medicine is characterized by its inherent uncertainty, i.e., the difficulty of identifying and obtaining exact outcomes from available data. Electronic Health Records (EHRs) aim to improve the exactitude of health management, for instance using automatic data recording techniques or the integration of structured as well as unstructured data. However, this data is far from perfect and is usually noisy, implying that epistemic uncertainty is almost always present in all biomedical research fields. This impairs the correct use and interpretation of the data not only by health professionals but also in modeling techniques and AI models incorporated in professional recommender systems. Method: In this work, we report a novel modeling methodology combining structural explainable models, defined on Logic Neural Networks (LONNs) which replace conventional deep-learning methods with logical gates embedded in neural networks, and Bayesian Networks (BN) to model data uncertainties. This means, we do not account for the variability of the input data, but we train single models according to the data and deliver different LONN models that could adapt to the input data, for instance, medical procedures (Therapy Keys (TK)) depending on the inherent uncertainty of the observed data. Result: Thus, our model does not only aim to assist physicians in their decisions by providing accurate recommendations; it is above all a user-centered solution that informs the physician when a given recommendation, in this case, a therapy, is uncertain and must be carefully evaluated. As a result, the physician must be a professional who does not solely rely on automatic recommendations. This novel methodology was tested on a database for patients with heart insufficiency and can be the basis for future applications of recommender systems in medicine.